Known unknowns and unknown unknowns in suicide risk assessment: Evidence from meta-analyses of aleatory and epistemic uncertainty. (June 2017) - Large, Matthew; Galletly, Cherrie; Myles, Nicholas; Ryan, Christopher James; Myles, Hannah
Summary: Suicide risk assessment aims to reduce uncertainty in order to focus treatment and supervision on those who are judged to be more likely to die by suicide. In this article we consider recent meta-analytic research that highlights the difference between uncertainty about suicide due to chance factors (aleatory uncertainty) and uncertainty that results from lack of knowledge (epistemic uncertainty). We conclude that much of the uncertainty about suicide is aleatory rather than epistemic, and discuss the implications for clinicians.